Tuning the surface segregation composition of a PdCo alloy by the atmosphere for increasing electrocatalytic activity. Issue 1 (5th November 2019) - Li, Tongtong; Wang, Rong; Yang, Minghe; Zhao, Shuaishuai; Li, Zhijie; Miao, Junjian; Gao, Zhi-Da; Gao, Yi; Song, Yan-Yan
Abstract : The surface composition of PdCo alloy was tuned by the annealing atmosphere. By electrochemical etching Co atoms, the alloy with Pd-rich surfaces was rearranged with abundant high-index facets, which leads to an enhanced HER performance. Abstract : The rational design of active sites for electrocatalysts is crucial for achieving high efficiency of electrochemical reactions. Contrary to the shape-controlled method, herein, we reported a selective segregation-etching strategy to highly increase the active sites of a bimetallic alloy as a high-performance electrocatalyst. The surface composition of the PdCo alloy was manipulated by its preferential segregation in the atmosphere according to the predictions of the density functional theory (DFT). By leaching Co atoms from the surface having a balanced composition with consecutive potential cycling in an acid solution, the surface reconstructed to show a high density of high-index Pd facets identified by Cs-corrected transmission electron microscopy. Using hydrogen evolution as a model reaction, the resulting catalyst exhibited enhanced electrocatalytic activity and outstanding long-term stability. This study provides a general principle to design a transition metal alloy with highly active sites, which has a great potential in broad areas such as batteries, fuel cells, and beyond.